Age associated decline in the arcuate fasciculus and IQ. - Ikuta, Toshikazu; Gollnick, Hannah M.; Rutledge, Anna N. (Brain Imaging & Behavior, 2020)
The arcuate fasciculus (AF) has been implicated in its association with intelligence. Probabilistic tractography on diffusion tensor imaging (DTI) data provides isolation of white matter tracts between two distant cortical structures. In this study, we performed probabilistic tractography between Wernicke's and Broca's area in the left and right hemisphere, to examine the association of the arcuate fasciculus's integrity with age and intelligence, using DTI data from 488 individuals whose age ranges between 6 to 85 years. The left, but not right, AF showed significant decline with age. Both left and right AF showed significant association with the full-scale IQ measured by the Wechsler Abbreviated Intelligence Scale. Both fasciculi showed significant association with the subscale verbal IQ, but only the left showed performance IQ. This study demonstrates that the bilateral arcuate fasciculi are associated with IQ; left vs. right asymmetry is present in its aging and function.